2011
DOI: 10.1016/j.pain.2011.02.019
|View full text |Cite
|
Sign up to set email alerts
|

ONO-8130, a selective prostanoid EP1 receptor antagonist, relieves bladder pain in mice with cyclophosphamide-induced cystitis

Abstract: Given the previous evidence for involvement of prostanoid EP1 receptors in facilitation of the bladder afferent nerve activity and micturition reflex, the present study investigated the effect of ONO-8130, a selective EP1 receptor antagonist, on cystitis-related bladder pain in mice. Cystitis in mice was produced by intraperitoneal administration of cyclophosphamide at 300mg/kg. Bladder pain-like nociceptive behavior and referred hyperalgesia were assessed in conscious mice. Phosphorylation of extracellular si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
50
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 37 publications
5
50
0
Order By: Relevance
“…There is a report that intravenous administration of EP1 antagonist relieved bladder pain in cystitis model rats. 7 However, there have been few studies that investigated the pathophysiological role of PGE2 in patients with IC/BPS. To our knowledge, no single study has ever investigated the involvement of PGE2 and EP receptors in different subtypes of IC/BPS.…”
Section: Textmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a report that intravenous administration of EP1 antagonist relieved bladder pain in cystitis model rats. 7 However, there have been few studies that investigated the pathophysiological role of PGE2 in patients with IC/BPS. To our knowledge, no single study has ever investigated the involvement of PGE2 and EP receptors in different subtypes of IC/BPS.…”
Section: Textmentioning
confidence: 99%
“…11,12 Systemic administration of EP1 antagonist attenuates esophageal hyperalgesia in human and bladder pain in cystitis model mice. 7,13 Regarding EP1 receptor and bladder function, it is suggested that intravesical PGE2 promotes micturition reflex by stimulating C-fiber afferent nerves via EP1 receptor. 14,15 These previous studies and the present study indicate that the action of PGE2 via EP1 receptor has an important role in the development of bladder pain and urinary frequency in ulcer-type IC/BPS.…”
mentioning
confidence: 99%
“…53,54) We have shown that ONO-8130, a selective EP 1 receptor antagonist, reverses bladder pain-like behavior and referred hyperalgesia in mice with cyclophosphamide-induced cystitis, and prevents prompt phosphorylation of ERK in the spinal dorsal horn following intravesical administration of PGE 2 . 55) There is also evidence for involvement of peripheral EP 3 receptors in the regulation of bladder micturition and bladder nociception. 56) Thus, selective antagonists of EP 1 receptors and, perhaps, EP 3 receptors may be useful for treatment of visceral pain including esophageal and/or bladder pain.…”
Section: Application Of Pge 2 Receptor Antago-nists To Treatment Of Vmentioning
confidence: 99%
“…Thus pain hypersensitivity is attenuated in EP1-deficient mice (25) and after systemic or intrathecal administration of EP1 receptor antagonists (16,19). In the rodent viscera, EP1 receptor antagonists inhibit bladder afferent nerve activity during bladder inflammation and attenuate cystitis-related bladder pain (10,14). Furthermore, there is preclinical evidence that prior systemic treatment with an EP1 receptor antagonist attenuates acid-induced primary and secondary esophageal hyperalgesia in humans (24).…”
mentioning
confidence: 99%